NORMAL PHYSIOLOGICAL PROCESSES OF THE DIGESTIVE SYSTEM - Xidoyat S. Abdullayeva (International Journal of Literature and Language Studies, 2026)
This article examines the normal physiological processes of the digestive system, its structure, and functional significance. The movement of food through the gastrointestinal tract, beginning in the oral cavity and continuing through the stomach and intestines, is described. The mechanisms of mechanical and chemical digestion, nutrient absorption, and the role of digestive enzymes, hormones, and nervous regulation are analyzed based on scientific literature. The importance of the digestive system in maintaining human health, metabolic balance, and vital body functions is also discussed.